MEMUKUL WAJAH DALAM PERSPEKTIF HADIS DAN RELEVANSINYA DENGAN BUDAYA SUKU MANDAR - Al-Mandary, Haerul; Muin, Firdaus; Nawas, Sitti Syakirah Abu; Amiruddin, Andi Muhammad Ali; Abdul Rauf, Rusmin (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
This article examines the prohibition of striking the face from the perspective of ḥadīth using the ma‘ānī al-ḥadīth approach and its relevance to Mandar culture. The objectives of this study are to examine the authenticity of the ḥadīth concerning the prohibition of striking the face, analyze its semantic meanings, and explain its relevance to Mandar cultural values. This research employs a qualitative method based on library research. The analytical framework applies the ma‘ānī al-ḥadīth approach through three interpretive methods: textual, intertextual, and contextual interpretation, integrated with a cultural studies approach. In addition, ḥadīth takhrīj methods are employed to trace and assess the authenticity of the ḥadīth under study. The findings indicate that the ḥadīth transmitted through the sanad of Imām Aḥmad ibn Ḥanbal is classified as ṣaḥīḥ li-dhātihi, as it fulfills all criteria of authenticity. Textually and intertextually, the ḥadīth demonstrates a firm prohibition against all forms of violence, while contextually it encompasses both physical and verbal violence. This prohibition is consistent with Mandar cultural values that uphold siri’, emphasizing the protection of human dignity and honor.